PEMAKNAAN AYAT MENURUT HARUN NASUTION DALAM BUKU ISLAM DITINJAU DARI BERBAGAI ASPEKNYA - Humaidi, Riki; Alkadri, Alkadri; Sunandar, Sunandar (Borneo : Journal of Islamic Studies, 2024)
Harun Nasution is a Muslim scholar who was able to change the exclusive perspective of Islam to an inclusive one, as evidenced by the market acceptance of the book "Islam Ditinjau dari Berbagai Aspeknya." In this book, the author interprets numerous verses from the Qur'an to address the socio-religious issues of the time, despite not having a background in interpretation. Instead, the author is a scholar who favors more fundamental philosophical thinking. The goal of this study is to interpret the meaning of the Koranic verses found in Islamic books from a variety of perspectives. This research is based on the literature and employs qualitative methods. The book "Islam Ditinjau dari Berbagai Aspeknya" serves as the primary data source for this study, with secondary data sourced from relevant books, journals, theses, and other scientific articles. The data collection technique was carried out by making a general mapping of the verses used in the book and analyzing the meaning of the verses used by Harun Nasution using the bil ma'tsur method. The study's results reveal that Harun Nasution employs a variety of textual and historical perspectives in his discussions, as evidenced by his interpretation of verses from the Koran in his works. The verse's contextualization does not entirely align with the original text's meaning. In addition, he employs a variety of philosophical approaches in his interpretation, as demonstrated in the text. To elucidate the verses of the Koran on this theme, he references the perspectives of Sufism